A Vietnamese Royal Exile in Japan: Prince Cuong De (1882-1951) - My-Van, Tran (Routledge, 2020)
Prince Cuong De, viewed by the French as a pretender to the Vietnamese throne, was an important and interesting figure in the history of Vietnam’s struggle for independence. He was highly regarded by many non-communist Vietnamese nationalists, but has been virtually ‘written out’ of Vietnamese history.